2008
DOI: 10.1111/j.1365-2389.2008.01063.x
|View full text |Cite
|
Sign up to set email alerts
|

Water flow paths in soil control element exports in an Andean tropical montane forest

Abstract: We tested the hypothesis that concentrations of chemical constituents in stream water can be explained by the depth of water flow through soil. Therefore, we measured the concentrations of total organic carbon (TOC), NO 3 -N, NH 4 -N, dissolved organic nitrogen (DON), P, S, K, Ca, Mg, Na, Al and Mn in rainfall, throughfall, stemflow, litter leachate, mineral soil solution and stream water of three 8-13 ha catchments on steep slopes (1900-2200 m above sea level) of the south Ecuadorian Andes, from April 1998 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
91
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(108 citation statements)
references
References 52 publications
11
91
1
2
Order By: Relevance
“…3). As weather conditions in WET were likely to lead to episodic water saturation favoring lateral flow in topsoil (Boy et al 2008b) Mandernack et al 2000). The denit values of Mandernack et al (2000) are not directly comparable to ours because the authors reported the fractionation of several chemical reaction steps while we report fractionation during the first reaction step only.…”
Section: Seasonal Variability Of N Transformationscontrasting
confidence: 49%
See 1 more Smart Citation
“…3). As weather conditions in WET were likely to lead to episodic water saturation favoring lateral flow in topsoil (Boy et al 2008b) Mandernack et al 2000). The denit values of Mandernack et al (2000) are not directly comparable to ours because the authors reported the fractionation of several chemical reaction steps while we report fractionation during the first reaction step only.…”
Section: Seasonal Variability Of N Transformationscontrasting
confidence: 49%
“…DRY than in WET. Furthermore, lateral flow in the organic layer following water saturation of the soil is important at our study site (Goller et al 2005;Boy et al 2008b), which is likely to have occurred in WET. Lateral flow might have flushed NH 4 + quickly to the stream and consequently reduced its availability.…”
Section: Seasonal Variability Of N Transformationsmentioning
confidence: 99%
“…We therefore conclude that the observed signatures were caused by shallow sub-surface flow during rainfall events, which agrees with findings in NF by Jacobs et al (in review) and is commonly observed in tropical montane forested catchments (e.g. Boy et al, 2008;Muñoz-Villers and McDonnell, 2012;Saunders et al, 2006). The extent to which the Hydrol.…”
Section: Dominant Water Sources 20supporting
confidence: 81%
“…[Wilcke et al, 2001;Boy et al, 2008b]. Our own records show that annual precipitation ranged between 2000 and 2500 mm and that mean annual temperature was 14.9°C during 1999-2010.…”
Section: Study Sitementioning
confidence: 99%